Supportive Social Interactions in Infertility Treatment Decrease Cortisol Levels: Experimental Study Report - Malina, Alicja; Głogiewicz, Małgorzata; Piotrowski, Jakub (Frontiers in Psychology, 2019)
Purpose The aim of the research project was to analyze the importance of supportive social interactions in the process of infertility treatment. The acceptance rates of ART (Assisted Reproductive Technology) in Poland are lower than in western European countries and the social stigma of infertility exists. The research project draws attention to the issue of disclosure of fertility problems and the ability to seek support in Polish couples. Methods An experimental study was conducted with 51 heterosexual couples who qualified for IVF. The participants were randomly divided into an experimental and control group. The first stage of the research procedure, with all the couples, was to extract a saliva (cortisol) sample as a biomarker for stress. In the second stage the control group viewed an informational (non-emotional) video about human embryology. The experimental group took part in a supportive social interaction process. In the supportive social interaction process, a maximum of five couples, were led through a broad general understanding of their IVF experience by an experienced group psychologist. The third stage of the research involved the second extraction of a saliva (cortisol) sample form all participants. In addition, demographic and medical history related to fertility was collected. Results The statistical analysis indicates a significant decrease in the level of stress experienced after the supportive social interaction. The reported differences between the experimental group and the control group indicated a larger decrease of cortisol level for women and men. Conclusion In the current study, the hypothesis that taking part in supportive social interaction significantly lowers stress levels (measured via cortisol) of infertile couples (men and women) was supported. Further the project indicates that a supportive social interaction has a beneficial effect on infertile couple’s health and well-being. The results of the study clearly point to the benefits of couples involved in infertility treatment to express and share their experience, and in doing so, provides measurable physiological and psychological benefits.